(untitled) (Contemporary Journal of Social Science Review, 2024)
Populism and polarization are interlinked phenomena that have transformed the global political landscape by manifesting divisive and conflictive rhetoric, leading them to undermine democratic institutions. This paper underscores the need to address the root causes such as economic grievances, identity politics, and ideological division that have precarious impacts on societies. This research seeks to uncover these common patterns and divergent outcomes and argues that personification, media environment, and economic strengths critically influence how populism and polarization unfold in different countries. This paper argues populism inherently fosters political polarization by deepening divisions in society This is a qualitative interpretative research study that uses exploratory and explanatory research designs. The theoretical framework incorporates theories of populism, political polarization, media and communication, and social constructivism. This paper recommends fostering inclusive political dialogue, addressing the root cause, and promoting media literacy are essential steps towards reducing and mitigating polarization and strengthening democratic institutions.